(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Hoesain M, Prastowo S, Suharto, Pradana AP, Asyiah IN, Alfarizy FK, Adiwena M. 2021. Combination of plant growth-promoting bacteria and botanical pesticide increases organic red rice yield and reduces the Leptocorisa acuta population. Biodiversitas 22: 1686-1694. Organic red rice production faces similar constraints as conventional rice production, namely pest attacks, especially rice earhead bugs (Leptocorisa acuta). The use of synthetic chemical inputs is also not allowed in organic red rice production. This problem can be overcome with the application of botanical pesticides, but the use of botanical pesticides do not promote plant growth. As a solution, a combination formula of plant growth-promoting bacteria and botanical pesticides is required. This study aimed to examine the effectiveness of a combination of plant growth-promoting bacteria with botanical pesticides in increasing the growth and yield of organic red rice plants and reducing the rice earhead bug population. The research was conducted on organic agricultural land in Jember Regency, Indonesia. The research began with the extraction of botanical pesticides from the leaves of Azadirachta indica, Aglaia odorata, and Ageratum conyzoides using 96% ethanol. The bacterial isolates obtained and characterized in previous studies were tested for their compatibility and cell viability in the combination formula. The field experiment was conducted with 8 treatments, 3 replications, and each replication consisted of 150 rice plants. The randomization pattern followed a randomized block design pattern. The results showed that all bacteria were compatible when combined with 20% botanical pesticides. In addition, cell viability at 3 months of storage decreased, but not significantly. In the organic rice growth variable, all combinations of bacteria with botanical pesticides showed good performance to increase the plant growth. Increased plant growth occurred in the number of tillers, plant height, and the number of productive panicles. Furthermore, yield variables, fresh seed weight per panicle, dry seed weight per panicle, and weight of 1000 seeds also increased significantly after being treated with a combination of plant growth-promoting bacteria and botanical pesticides. The decline in the rice earhead bug population also occurred in all plants treated using botanical pesticides either singly or in combination. The best treatments in this study were BS01 and PD01, which showed consistent results. This study provides information that the combination of plant growth-promoting bacteria and botanical pesticides is compatible, does not cause a high number decrease of bacterial cells at a shelf-life of 3 months, and can stimulate the growth and yield of organic red rice, and can suppress rice earhead bug populations.